Disclosure of Corporate Social Responsibility and the factors that influence it: Evidence in Indonesia - Raden Arief Wibowo (Profesional Muda Cendekia Publishing, 2021)
The purpose of this study begins with an analysis to see how the disclosure of corporate social responsibility during the covid19 pandemic, then continues with an analysis to see what factors affect the disclosure of corporate social responsibility. This study uses a sample of 150 non-financial companies listed on the IDX in 2012-2020. The analytical tool used in this study is panel data regression with a random effect model. The results showed that the variables of audit committee composition, ownership concentration, management participation, return on assets, return on equity, debt and number of employees did not have a positive effect on the disclosure of corporate social responsibility. Meanwhile, the variables of the board of commissioners meeting and the total balance sheet have a positive effect on the disclosure of corporate social responsibility.